KEMAMPUAN METAKOGNISI DAN HUBUNGANNYA DENGAN HASIL BELAJAR MAHASISWA MATA KULIAH FISIKA KUANTUM MATERI SIFAT PARTIKEL DARI GELOMBANG - MUKTAR B. PANJAITAN; ANDRIONO MANALU; RAYI D. M. SINAGA (JURNAL ILMIAH SIMANTEK, 2020)
The purpose of this research is to determine and describe metacognition knowledge, metacognition awareness and studentlearning outcomes in modern physics subject matter of particle properties from waves, odd semester of 2019/2020 schoolyear. Determination of the sample using the Simple Random Sampling technique. Data collection was carried out usingwritten tests in the form of a description to measure metacognition knowledge and awareness questionnaires using theMetacognition Awareness Inventory (MAI). Learning that is carried out with stages of representation, analogy, givingexamples and reflection can improve student learning outcomes with an average n-gain of 0.63. The t-test results showedthat there was a significant difference between the pretest and posttest scores (sig. = 0,000). Correlation test shows apositive relationship with r = 0.40 between declarative metacognitive knowledge and learning outcomes. The correlationbetween procedural metacognitive knowledge and learning outcomes is 0.44. While the relationship between conditionalmetacognitive knowledge and learning outcomes is 0.37. The relationship between MAI with learning outcomes of 0, 34.Lecturers can use learning with the stages of presentation, analogy, examples of solutions and reflection in an effort toimprove learning outcomes and pay attention to students' knowledge and awareness of metacognition.